12. Canadian Educational Development Centre Websites: More Ebb Than Flow? - Nicola Simmons (Collected Essays on Learning and Teaching, 2011)
This paper examines information portrayed on Canadian educational development (ED) centre websites and, in particular, whether information that corresponds to questions compiled from a literature search of ED centre practices is readily available from centre websites. This study phase is part of a larger national study of Canadian educational development centres’ practices.